2004
DOI: 10.1074/jbc.m308528200
|View full text |Cite
|
Sign up to set email alerts
|

NH3 Is Involved in the NH4+ Transport Induced by the Functional Expression of the Human Rh C Glycoprotein

Abstract: Renal ammonium (NH 3 ؉ NH 4 ؉ ) transport is a key process for body acid-base balance. It is well known that several ionic transport systems allow NH 4 ؉ transmembrane translocation without high specificity for NH 4 ؉ , but it is still debated whether NH 3 , and more generally, gas, may be transported by transmembrane proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
154
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(170 citation statements)
references
References 33 publications
13
154
2
1
Order By: Relevance
“…Similar studies in RhCG-expressing oocytes have concluded that RhCG could mediate electrogenic transport that is consistent with NH 3 and NH 4 + enhanced influx [14]. The discrepancies between these studies might be explained by the different methodologies used and by the existence of an ammonium-activated endogenous transport pathway in oocytes [18,19] that could hamper more precise analysis of an exogenous ammonium transporter.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similar studies in RhCG-expressing oocytes have concluded that RhCG could mediate electrogenic transport that is consistent with NH 3 and NH 4 + enhanced influx [14]. The discrepancies between these studies might be explained by the different methodologies used and by the existence of an ammonium-activated endogenous transport pathway in oocytes [18,19] that could hamper more precise analysis of an exogenous ammonium transporter.…”
Section: Introductionmentioning
confidence: 79%
“…A recent study also identified RhBG and RhCG as having a cell specific, axially heterogeneous and polarized expression in the gastrointestinal tract [13]. As is the case for RhAG, ammonium transport activity of RhCG was first shown by complementation studies in yeast [5] and then confirmed by functional studies in Xenopus oocytes [14]. RhBG-mediated ammonium transport was also recently demonstrated in the Xenopus oocyte expression system [15,16].…”
Section: Introductionmentioning
confidence: 90%
“…In the absence of heterologously expressed ammonia channels, this response to ammonia influx is seen only above about 1 mM external NH 4 + at pH 7.5 [5,23]. The significant currents seen in RhBG [32] and RhCG oocytes [2] at even lower concentrations may, therefore, be the consequence of RhBG/RhCG-enhanced NH 3 permeability rather than proof of NH 4 + transport. All the studies with heterologously expressed Rh proteins appear compatible with their functioning as NH 3 channels.…”
Section: Rh-mediated Ammonia Transport In Animal Cellsmentioning
confidence: 88%
“…Functional studies with RhAG, RhBG, and RhCG have been carried out by expression in oocytes [2,23,32,47], and in ammonium transport deficient S. cerevisiae [27,48]. They have been interpreted in terms of NH 4 + transport [27,32], influx of both NH 3 and NH 4 + ([2] and NH 4 + /H + exchange [23,47,48].…”
Section: Rh-mediated Ammonia Transport In Animal Cellsmentioning
confidence: 99%
“…RhAG expression is restricted to the erythrocyte membrane, whereas RhBG and RhCG are expressed in various tissues in the mammalian systems, including liver, kidney and gastrointestinal tract (Handlogten et al, 2005;Liu et al, 2000;Liu et al, 2001;. Studies in mammalian and plant systems reveal that at least some of those Rh genes encode proteins that mediate NH 3 /NH 4 + movement (Khademi et al, 2004;Zheng et al, 2004;Mayer et al, 2006), but the form of ammonia (NH 3 gas or NH 4 + ion) being transported, and whether the transport is active or passive, are still under much debate (Bakouh et al, 2004;Khademi et al, 2004;Nakhoul et al, 2005). A fulllength cDNA of Rh-like protein (Rh-CM) has been identified recently from the gills of the aquatic crab Carcinus maenas, which has a similar predicted transmembrane structure as the mammalian Rh proteins (Weihrauch et al, 2004).…”
Section: Introductionmentioning
confidence: 99%